Systematic analysis of the Frazzled receptor interactome establishes previously unreported regulators of axon guidance. - Zang, Y.; Bashaw, G.J. (Development, 2023)
The Netrin receptor Dcc and its Drosophila homolog Frazzled play crucial roles in diverse developmental process, including axon guidance. In Drosophila, Fra regulates midline axon guidance through a Netrin-dependent and a Netrin-independent pathway. However, what molecules regulate these distinct signaling pathways remain unclear. To identify Fra-interacting proteins, we performed affinity purification mass spectrometry to establish a neuronal-specific Fra interactome. In addition to known interactors of Fra and Dcc, including Netrin and Robo1, our screen identified 85 candidate proteins, the majority of which are conserved in humans. Many of these proteins are expressed in the ventral nerve cord, and gene ontology, pathway analysis and biochemical validation identified several previously unreported pathways, including the receptor tyrosine phosphatase Lar, subunits of the COP9 signalosome and Rho-5, a regulator of the metalloprotease Tace. Finally, genetic analysis demonstrates that these genes regulate axon guidance and may define as yet unknown signaling mechanisms for Fra and its vertebrate homolog Dcc. Thus, the Fra interactome represents a resource to guide future functional studies.